Antibacterial activity of ethanolic extract and fraction of leaves of singawalang (Petiveria alliaceae) against resistant bacteria - Mulyani, Yani; Sukandar, Elin Yulinah; Adnyana, I Ketut (INDONESIAN JOURNAL OF PHARMACY, 2011)
One  of the plants  that grow  in Indonesia,  and  still does  not  use widely  is singawalang  (Petiveria  alliaceae)  from  Phytolaceae  family.  Traditional   herbal medicine  preparations  contained  of  Petiveria  alliacea  in  the  Caribbean,  Latin America,  West  Africa  and  other  regions  for  hundreds  years  has  been  used  to treat  pain,  colds,  inflammation,  tumor,  bacterial  and  fungal   infection,hyperlipidemia,  diabetes and  other  diseases.  This  study  aims to determine  the antibacterial  activity  of  singawalang  growth  in  Indonesia  against  resistant bacteria  to  antibiotics.  The  minimum  inhibitory  concentration   (MIC)  and minimum  bactericidal  concentration(MBC)  were  determined  by  microdilution broth method and type of antibacterial action were determined by observing the profile of bacterial growth curve. Ethanol extract of dried leaves showed activity against bacteria i.e. MRSA (Methicillin-Resistant Staphylococcus aureus), MRCNS (Methicillin-Resistant  Coagulase-Negative  Staphylococci),  VRE  (VancomycinResistant  Enterococcus).   Further  studies  conducted  by  reviewing  the  type  of work  by  looking  at the  growth curve  and  the observed changes  in cell walls by scanning  electron  microscopy  (SEM)  at  MRCNS  (Methicillin-Resistant Staphylococcus  coagulase-Negative).  The  results  showed  that  ethanol  extracts and  all  fractions  showed  good  antibacterial  activity  against  resistant  bacteria, are  bacteriostatic  hexane  fraction  until  the  concentration  of  8  MIC  and  change the morphology of the cell wall of MRCNS.Key words:Singawalang, Antibacteria, Broth Microdilution, bacterial growth curve, SEM